Chinese Learners’ Problems of Personal Pronouns: Who’s Who in Thai - Manomaivibool, Preena (Journal of Sinology (วารสารจีนวิทยา), 2010)
Personal pronouns in Thai language seem to be a problem for Chinese learners, especially the beginners who are not used to the Thai language culture of using the 1st and 2nd personal pronouns. This is because Thai language has a large number of personal pronouns and put into consideration the sex, number, age, social status, context and situation. While the 1st and 2nd personal pronouns in Mandarin Chinese have only 5 words, dividing only by number into the singular ones: 我，你，您and the plural ones: 我们，你们.Therefore, Chinese learners have to be careful in choosing the right Thai personal pronoun for each context.